2020
DOI: 10.1002/chem.202000346
|View full text |Cite
|
Sign up to set email alerts
|

Excited‐State Electron Transfer in 1,1,4,4‐Tetracyanobuta‐1,3‐diene (TCBD)‐ and Cyclohexa‐2,5‐diene‐1,4‐diylidene‐Expanded TCBD‐Substituted BODIPY‐Phenothiazine Donor–Acceptor Conjugates

Abstract: A new set of donor–acceptor (D–A) conjugates capable of undergoing ultrafast electron transfer were synthesized using 4,4‐difluoro‐4‐bora‐3a,4a‐diaza‐s‐indacene (BODIPY)‐substituted phenothiazine, SM1–SM3, by a Pd‐catalyzed Sonogashira cross‐coupling reaction and a [2+2] cycloaddition–electrocyclic ring‐opening reaction. The incorporation of 1,1,4,4‐tetracyanobuta‐1,3‐diene (TCBD) and cyclohexa‐2,5‐diene‐1,4‐diylidene‐expanded TCBD (abbreviated as DCNQ=dicyanodiquinodimethane) in BODIPY‐substituted phenothiazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 73 publications
1
41
1
Order By: Relevance
“…[42][43][44][45][46][47][48] The photochemical behavior of a few donor-TCBD derived systems have been reported in the literature. [49][50][51][52][53][54][55][56] Although with high quantum yields, due to close proximity between the donor and acceptor entities, ultrafast charge separation and recombination was observed in these systems. That is, no charge stabilization could be accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46][47][48] The photochemical behavior of a few donor-TCBD derived systems have been reported in the literature. [49][50][51][52][53][54][55][56] Although with high quantum yields, due to close proximity between the donor and acceptor entities, ultrafast charge separation and recombination was observed in these systems. That is, no charge stabilization could be accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…An energy‐level diagram was established to comprehend different photoinduced events in supramolecular tetrad, as shown in Figure 7. Energies of different states were calculated according to the Rehm–Weller approach, [25] as explained in our previous work [26] . From the earlier discussed steady‐state fluorescence studies, singlet–singlet energy transfer from directly excited 1 BTZ* ( hν 1 ) to BODIPY in BTZ‐BODIPY, BTZ‐BODIPY‐ZnP, and BTZ‐BODIPY‐ZnP:ImC 60 systems was clear (EnT1).…”
Section: Resultsmentioning
confidence: 99%
“…An energy-level diagram was established to comprehend different photoinduced eventsi ns upramolecular tetrad, as shown in Figure7.E nergies of different states were calculated according to the Rehm-Wellera pproach, [25] as explained in our previousw ork. [26] From the earlier discussed steady-state fluorescence studies, singlet-singlet energy transfer from directly excited 1 BTZ* (hn 1 )t oB ODIPY in BTZ-BODIPY,B TZ-BODIPY-ZnP, and BTZ-BODIPY-ZnP:ImC 60 systems was clear (EnT1). 1 BODIPY*, which wasp roduced as the product of energy transfer or by direct excitation (hn 2 ), could follow at least four photochemical eventsc ompetitively,n amely,f luorescence emission, ISC to populate 3 BODIPY*, charges eparation with the neighboring ZnP to yield the BTZ-BODIPYC À -ZnPC + charge-separated state (CS3), or singlet-singlet energy transfer to yield BTZ-BODIPY-1 ZnP * :ImC 60 (EnT2).…”
Section: Energy Diagrammentioning
confidence: 93%
“…[8] Based on this concept, few groups have been successful in building push-pull conjugates. [9][10][11] Research teams of Bottari, Torres,a nd Guldi have also reported phthalocyanine-TCBD and subphthalocyanine-TCBD donor-acceptor (D-A) systems. [10] Our groups have reported af ew TCBD functionalized chromophores,a nd established excited state charge separation useful for optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Our groups have reported af ew TCBD functionalized chromophores,a nd established excited state charge separation useful for optoelectronic applications. [11] In general, in polar solvents,ICT transitions of push-pull systems occur at the low-energy side of the spectrum while that of LE transitions occur at the high-energy side of the spectrum. [6] This trend could be reversed if ahigh-energy ICT exhibiting species can be connected to anear-IR sensitizer.…”
Section: Introductionmentioning
confidence: 99%